(untitled) (مجلة الواحات للبحوث والدراسات, 2025)
Technological developments, economic transformations, changing institutional work mechanisms, the openness of institutions to their environment, the shift toward a knowledge economy, in which information has become as important as social capital, and the entry into the competitive market. Furthermore, the internal development of institutions—whether through their size and human resources, the development of their management and production systems, or the adoption of new technological techniques—have all contributed to the importance of communication within organizations. Communication has become a core function encompassing all other administrative functions, ensuring coordination and guidance among employees and between them and their clients, enabling them to achieve efficiency and effectiveness in their performance. Most organizations also seek to rely on knowledge management as a strategic requirement to ensure their survival and continuity. This is achieved by adopting mechanisms, approaches, and knowledge management methods that enable them to plan their efforts, activities, programs, and strategies to achieve their desired goals and improve their image and reputation with their customers. Hence, this Research Paper reveals the role of comprehensive communication as one of the most important fundamental approaches to knowledge management. It helps empower individuals to acquire knowledge through the practices and learning methods adopted by the organization. This enables them to become capable individuals who are able to confront new developments, find the best possible solutions to address them, and expand their horizons, which contributes to achieving sustainable performance. Keywords: Comprehensive Communication, Management, Knowledge, Sustainable Development.